Association of the Interaction Between Smoking and Depressive Symptom Clusters With Coronary Artery Calcification: The CARDIA Study. Issue 1 (2nd January 2017) - Carroll, Allison J.; Auer, Reto; Colangelo, Laura A.; Carnethon, Mercedes R.; Jacobs, David R.; Stewart, Jesse C.; Widome, Rachel; Carr, John Jeffrey; Liu, Kiang; Hitsman, Brian
ABSTRACT: Objective : Depressive symptom clusters are differentially associated with prognosis among patients with cardiovascular disease (CVD). Few studies have prospectively evaluated the association between depressive symptom clusters and risk of CVD. Previously, we observed that smoking and global depressive symptoms were synergistically associated with coronary artery calcification (CAC). The purpose of this study was to determine whether the smoking by depressive symptoms interaction, measured cumulatively over 25 years, differed by depressive symptom cluster (negative affect, anhedonia, and somatic symptoms) in association with CAC.Methods : Participants ( N = 3, 189: 54.5% female; 51.5% Black; average age = 50.1 years) were followed from 1985–1986 through 2010–2011 in the Coronary Artery Risk Development in Young Adults (CARDIA) study. Smoking exposure was measured by cumulative cigarette pack-years (cigarette packs smoked per day × number of years smoking; year 0 through year 25). Depressive symptoms were measured using a 14-item, 3-factor (negative affect, anhedonia, somatic symptoms) model of the Center for Epidemiologic Studies Depression (CES-D) Scale (years 5, 10, 15, 20, and 25). CAC was assessed at year 25. Logistic regression models were used to evaluate the association between the smoking by depressive symptom clusters interactions with CAC ( = 0 vs. > 0), adjusted for CVD-related sociodemographic, behavioral, and clinical covariates.Results : 907 participants (28% of the sample) had CAC > 0 at year 25. The depressive symptom clusters did not differ significantly between the two groups. Only the cumulative somatic symptom cluster by cumulative smoking exposure interaction was significantly associated with CAC > 0 at year 25 ( p = .028). Specifically, adults with elevated somatic symptoms (score 9 out of 18) who had 10, 20, or 30 pack-years of smoking exposure had respective odds ratios (95% confidence intervals) of 2.06 [1.08, 3.93], 3.71 [1.81, 7.57], and 6.68 [2.87, 15.53], p s < .05. Negative affect and anhedonia did not significantly interact with smoking exposure associated with CAC >0, p s > .05.Conclusions : Somatic symptoms appear to be a particularly relevant cluster of depressive symptomatology in the relationship between smoking and CVD risk.